Humor Assessment and Interventions in Palliative Care: A Systematic Review - Linge-Dahl, Lisa M.; Heintz, Sonja; Ruch, Willibald; Radbruch, Lukas (Frontiers in Psychology, 2018)
Background: The central goal of palliative care is to optimize the quality of life of patients suffering from life-limiting illnesses, which includes psychosocial and spiritual wellbeing. Research has demonstrated positive correlations between humor and laughter with life satisfaction and other aspects of wellbeing, and physiological symptoms can be improved by humorous stimuli. Objectives: The aim of this review is to evaluate humor interventions and assessments that have been applied in palliative care and to derive implications for future research. Methods: A systematic review of four databases identified 13 included studies. Criteria for inclusion were peer-reviewed English-language studies on humor interventions or assessments in a palliative care context. Results: Two studies on humor interventions and 11 studies on humor assessment were included in the systematic review. Most of these studies were about the patients’ perspective on humor in palliative care. Findings showed that humor had a positive effect on patients, their relatives, and professional caregivers. Humor was widely perceived as appropriate and seen as beneficial to care in all studies. Conclusions: Even though humor interventions seem to be potentially useful in palliative care, descriptions evaluating their use are scarce. Overall, research on humor assessment and interventions in palliative care has remained limited in terms of quantity and quality. More research activities are needed to build a solid empirical foundation for implementing humor and laughter as part of regular palliative care activities.